2021
DOI: 10.33594/000000432
|View full text |Cite
|
Sign up to set email alerts
|

The Intertwining of Autophagy and the Ubiquitin Proteasome System in Podocyte (Patho)Physiology

Abstract: Protein homeostasis strongly depends on the targeted and selective removal of unneeded or flawed proteins, of protein aggregates, and of damaged or excess organelles by the two main intracellular degradative systems, namely the ubiquitin proteasomal system (UPS) and the autophagosomal lysosomal system. Despite representing completely distinct mechanisms of degradation, which underlie differing regulatory mechanisms, growing evidence suggests that the UPS and autophagy strongly interact especially in situations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 188 publications
(248 reference statements)
0
6
0
1
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are a kind of proteolytic enzymes, whose main function is to degrade ECM. MMP-9 is a member of the MMPs family, also known as gelatinase, which can degrade gelatin, type IV collagen and type V collagen in ECM, thus destroying the structure of ECM, inducing EMT, and promoting tumor cell invasion and metastasis ( Heintz and Meyer-Schwesinger, 2021 ). Other studies ( Lazaar and Panettieri, 2005 ; Khodabakhshi et al, 2021 ) have shown that interleukin-1 β (IL-1 β) plays an important role in tumor growth, proliferation, invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are a kind of proteolytic enzymes, whose main function is to degrade ECM. MMP-9 is a member of the MMPs family, also known as gelatinase, which can degrade gelatin, type IV collagen and type V collagen in ECM, thus destroying the structure of ECM, inducing EMT, and promoting tumor cell invasion and metastasis ( Heintz and Meyer-Schwesinger, 2021 ). Other studies ( Lazaar and Panettieri, 2005 ; Khodabakhshi et al, 2021 ) have shown that interleukin-1 β (IL-1 β) plays an important role in tumor growth, proliferation, invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence suggests that dysregulation of the ubiquitin/proteasome system is strongly associated with autophagy [ 19 , 20 ]. In our study, LC3 immunofluorescence staining was positive (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this analysis, phagosomes were found to be involved. Research has indicated a close relationship between phagosomes, DN, and autophagy [39,40]. Additionally, specific lncRNAs, such as AK044604 (Risa), have been found to inhibit autophagy, exacerbating podocyte injury in DN [41].…”
Section: Discussionmentioning
confidence: 99%